Promosi Layanan Marketing Berbasis Pemasaran Holistik pada Literasi Media Digital Indonesia - Lady Faerrosa; Ahya Sarahya; Baiq Wanda Hamidah; Dafa Awanta (Insan Kreasi Media, 2023)
The ever-evolving internet technology is changing the way humans work and communicate. The Internet is also widely used as a supporter of the advancement of the creative communication service industry. The purpose of conducting this service is to assist developing a marketing strategy in promoting marketing services by using holistic marketing in order to create a more varied promotion strategy. The target of this activity is Indonesian Digital Media Literacy which is a relatively new digital communication service with a low number of employees. Hence, the authors see that Indonesian Digital Media Literacy still needs brainstorming ideas from other parties. Devotion in collaboration between the authors and Digital Media Literacy Indonesia in carrying out a branding strategy, gaining followers, and brand awareness to gain brand loyalty is very much needed by both parties. The author can implement the theory and knowledge of the marketing strategies studied. Meanwhile, an Indonesian Digital Media Literacy company gained insights and new strategies that have proven effective in increasing the number of social media followers it has and increasing the number of current clients.